Phenomenological Study of Mixue Products Using Viral Marketing Through Social Media - Andina, Anisa Nur; Vausi, Imam Nur; Fadillah, Al Bakhri Fajar Nur (Majalah Ilmiah Bijak, 2024)
Mixue ice cream and tea is an ice cream and tea shop that is currently being loved by consumers, especially those who are still students. The background to this research begins with the number of Mixue shops in Indonesia, especially in Purwokerto, which is starting to increase significantly. This research aims to find out how Mixue uses indirect viral marketing strategies to maintain its business. Researchers want to know how the viral marketing process is carried out by Mixue with a phenomenological study through interviews with informants and participant observation as well as the use of triangulation to check the validity of the data. It can be concluded from this research that Mixue carries out viral marketing indirectly because consumers who play a role in this do it for free. Consumers carry out viral marketing and spread it widely through their social media. Students like hanging out and doing assignments at Mixue because the atmosphere is good and it is more productive than doing assignments at campus or school.